2021
DOI: 10.1177/2473974x211059070
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Incidental Parathyroidectomy in a Pediatric Population

Abstract: Objective Incidental parathyroidectomy is a relatively common occurrence in thyroid surgery, which may lead to hypoparathyroidism and postoperative hypocalcemia, but it is not well studied in children. The objectives of this study were to determine the rate of incidental parathyroidectomy, identify potential risk factors, and investigate postoperative complications in children undergoing thyroidectomy. Study Design Retrospective cohort study. Setting Patients who underwent thyroidectomy over a 10-year period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The few complications that were reported are in accordance with the literature findings [ 3 , 13 , 16 , 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Infection of the wound is well-known and possible complications occur after every surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The few complications that were reported are in accordance with the literature findings [ 3 , 13 , 16 , 18 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Infection of the wound is well-known and possible complications occur after every surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
“…A literature review of eighteen articles dealing with thyroid surgery in paediatric population is shown in Table 3 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies (18) included in our literature review were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations